Exormotheca martins-loussaoae (Exormothecaceae, Hepaticae), a new species from Cape Verde. (4th March 2023) - Martins, Anabela; Garcia, César Augusto; Patiño, Jairo; Sim-Sim, Manuela
Abstract: Former phylogenetic evidence for the genus Exormotheca revealed the existence of a distinct and monophyletic clade restricted to the oceanic archipelago of Cape Verde. During the fieldwork carried out in Cape Verde between 2016 and 2019, we found distinctive populations of Exormotheca . In this study, we aim to investigate the Exormotheca pustulosa complex and its relationship to other Exormotheca species that coexist in the same geographical areas, using morphological characteristics, and to present a formal description of a new Exormotheca species from Cape Verde Archipelago. A total of 60 specimens belonging to Exormotheca genus were examined. The specimens included samples, with broad taxonomic coverage of the E. pustulosa species, as well as from two phylogenetically close taxa E. holstii, and E. welwitschii . The characters studied were selected based on previous works that describe and distinguish species within the genus Exormotheca, and from our own observations. A new species, Exormotheca martins-loussaoae from Cape Verde is described. The new species can be recognized by the dark green color of the thallus and the almost entire dark purple scales, and the thallus surface having 6 − 9 regular rows with large conical air chambers, occupied by a thin assimilation tissue.